The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1016/s2468-2667(18)30009-4
|View full text |Cite
|
Sign up to set email alerts
|

Front-of-pack Nutri-Score labelling in France: an evidence-based policy

Abstract: Propositions pour un nouvel élan de la politique nutritionnelle française de santé publique dans le cadre de la stratégie nationale de santé. 1ère partie: mesures concernant la prévention nutritionnelle. 2014. http://www. ladocumentationfrancaise.fr/rapports-publics/ 144000068/index.shtml (accessed Jan 4, 2018). 6 Julia C, Hercberg S. Development of a new front-of-pack nutrition label in France: the five-colour Nutri-Score. Public Health Panorama 2017; 3: 712-25. 7 WHO Europe. France becomes one of the first c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
82
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 113 publications
(100 citation statements)
references
References 1 publication
1
82
0
1
Order By: Relevance
“…80 This logo has been introduced in France and recently in Belgium. 81 Countries such as Spain and Portugal are considering this logo. The European consumer organisation (BEUC) supports this system, while the European Heart Network continues to recommend the traffic light system.…”
Section: Healthy Dietmentioning
confidence: 99%
“…80 This logo has been introduced in France and recently in Belgium. 81 Countries such as Spain and Portugal are considering this logo. The European consumer organisation (BEUC) supports this system, while the European Heart Network continues to recommend the traffic light system.…”
Section: Healthy Dietmentioning
confidence: 99%
“…The latest WHO catalogue lists more than 65 current nutrient profiling models and a more recent literature review indicated that 78 models have been released in the past 10 years . These include industry‐led schemes such as the Choices International's Programme, government‐endorsed schemes such as the UK's multiple traffic light labeling criteria and France's Nutri‐Score as well as nutrient profiling models developed for internal use by food and beverage manufacturers. Another use of nutrient profiling is to determine which foods are eligible to make a health or nutrition claim on product packaging, for example, the Nutrient Profiling Scoring Criterion developed by Food Standards Australia New Zealand…”
Section: Introductionmentioning
confidence: 99%
“…Today multiple environmental impact indicators exist, each focusing on a certain aspect of the environmental impact equation. As previously shown in the nutrition world, in order to successfully drive consumer behavior and engage multiple stakeholders, the creation of composite markers that weigh the different aspects and serve as a simple to use metric to compare one food to another will be needed (61)(62)(63). The science of nutrient pro ling was developed in nutrition for this purpose (64) and a similar discipline might soon be needed in the environmental sciences.…”
Section: Discussionmentioning
confidence: 99%